Adjusting to life during a pandemic. Issue 3 (16th June 2020) - Miles, David
Abstract : This article will deal with the pandemic and one university's response. I am sure everyone has their own story, but I am from a town in New Jersey that was called the epicenter of the virus in the early stages of its spread.